2021
DOI: 10.33448/rsd-v10i3.13354
|View full text |Cite
|
Sign up to set email alerts
|

Árvores de decisão baseadas em entalpia para avaliação de conforto para poedeiras leves em clima tropical

Abstract: Com o avanço da tecnologia foi possível armazenar uma grande quantidade de dados com um menor preço, sendo possível investigar os fatores climáticos que afetam a produção animal. A região Oeste do Estado de São Paulo é uma região propensa à ocorrência de extremos de temperatura, sendo um fator preocupante para os produtores de ovos. Neste estudo objetivou-se saber se é possível gerar árvores de decisão a partir de dados de entalpia utilizando a Mineração de Dados, e se estas árvores estarão aptas a serem inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The importance of environmental quality is escalating, with factors like ventilation and humidity, which directly influence air and litter quality, requiring control throughout the rearing period until the age of slaughter. Numerous studies have shown that elements such as temperature, relative air humidity, and air velocity assist birds in heat dissipation, thereby aiding them in maintaining their comfort enthalpy (Harada et al, 2021). Andrade et al (2018) posited that optimal bird productivity is achieved in farms that meet welfare requirements, thereby promoting the birds' physical and mental health as well as thermal comfort.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of environmental quality is escalating, with factors like ventilation and humidity, which directly influence air and litter quality, requiring control throughout the rearing period until the age of slaughter. Numerous studies have shown that elements such as temperature, relative air humidity, and air velocity assist birds in heat dissipation, thereby aiding them in maintaining their comfort enthalpy (Harada et al, 2021). Andrade et al (2018) posited that optimal bird productivity is achieved in farms that meet welfare requirements, thereby promoting the birds' physical and mental health as well as thermal comfort.…”
Section: Resultsmentioning
confidence: 99%
“…Heat stress, which can induce physiological issues and impact the endocrine and respiratory systems as well as the electrolyte balance of birds, is linked to the development and productivity of farms (Harada et al, 2021). Abreu et al (2015) asserted that birds require a suitable environment to achieve their productive potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the literature, the ideal enthalpy index intervals were verified, according to the characteristics of the birds, adapted from studies by Macari and Furlan, 2001;Barbosa Filho et al, 2007 andHarada et al, 2021 (Tables 1 and 2). Next, the procedures for data analysis were performed with the aid of the R Program (R CORE TEAM, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, knowledge of these climatic variables is relevant to support the design of the facilities and define elements such as orientation, materials, and ventilation system. Among other criteria, the thermal conditions in poultry facilities have been evaluated based on the enthalpy index (MACARI and FURLAN 2001, BARBOSA FILHO et al 2007, NAZA-RENO et al 2009, GARCIA et al 2015, AKAMINE and PASSINI 2017, BENINCASA et al 2017, QUEIROZ et al 2017, FERRAZ et al 2018, ROMANO et al 2018, SILVA et al 2018, HARADA et al 2021. Thus, this study is based on the hypothesis that the cited index can qualify the thermal environment to assist in the construction of poultry facilities.…”
Section: Introductionmentioning
confidence: 99%